MENINGKATKAN KINERJA GURU BIDANG STUDI MELALUI PENYUSUNAN RPP DENGAN TEKNIK LESSON STUDY KOLABORATIF - herlina, herlina (Program Studi Pendidikan Vokasi Seni Kuliner, 2023)
This research aims to determine the improvement in the performance of teachers in the field of study throught preparing lesson plans using collaborative and routine lesson study techniques at SMPN 6 Muaro Bungo. This research is school action research (PTS) using a qualitative approach. The research subjects in the study were social studies teachers and civics teachers. The research period was carries out from 08 October 2022 to 04 November 2022. Research procedures included research planning, research implementation, observation and reflection. The result of the research show that the preparation of lesson plans using the lesson study techique collaboratively and regularly is able to form productive and professional teaching staff in improving the quality of learning, and also effort to increase the performance of teachers in the field of study through the preparationof lesson plans using the lesson study techniques collaboratively and regularly have a big influence on student activities and learning outcomes.